Early stages of unwinding of zwitterionic alpha-helical homopolymeric peptides - Pandey, Prithvi Raj; Roy, Sudip (Chemical Physics Letters, 2011)
Unwinding mechanisms of helices of the zwitterionic polyalanine, polyleucine, and polylysine were studied using classical molecular dynamics simulation at 300 K temperature. Interestingly the helices of polyalanine and polyleucine start to unwind from the terminals, which is further relayed to the middle of the chain with time. Polylysine helix also starts to unwind from the terminals of the alpha-helical chain but the unwinding is not relayed to the middle. The reason behind this observation is investigated whether the presence of -NH(2) groups in the side chain of polylysine is influencing the unwinding. Two competitive mechanisms, fluctuation of the terminal residues and exchange of H-bonds between residues and water trigger the process of unwinding. (C) 2011 Elsevier B. V. All rights reserved.

Evidence and characterization of dynamic heterogeneity in binary mixtures of phosphoric acid and benzimidazole - Pahari, Swagata; Roy, Sudip (Journal of Chemical Physics, 2013)
We report here anomalous diffusions of components in mixtures of monomer of polybenzimidazole, i.e., 2-phenyl-1H, 1'H-5,5'-bibenzo[d] imidazole (BI) and phosphoric acid (PA) from molecular dynamics simulations. We have observed initial drop and further increase in self-diffusion constant for both monomer molecule (BI) and PA with gradual increase in PA concentration. The origin of such anomalous diffusion is identified in this work, which happens to be the presence of dynamic heterogeneity in each component of the binary mixture. We characterized microscopic picture of dynamical heterogeneity by finding correlation between dynamical heterogeneity and structural arrangement among the components of the binary system. Different types of H-bonding arrangements in the BI-PA systems at different concentration of PA are observed. The stability of the H-bonded network consisting of different types of H-bonds between BI and PA in the system has been studied by calculating the lifetime of various H-bonds. The results indicate that there are fast and slow moving PA molecules in the mixtures because of coexistence of different types of hydrogen bonds among the components of the mixture. (C) 2013 AIP Publishing LLC.

Effect of gold nanoparticle on structure and fluidity of lipid membrane - Mhashal, Anil R.; Roy, Sudip (Plos One, 2014)
This paper deals with the effect of different size gold nanoparticles on the fluidity of lipid membrane at different regions of the bilayer. To investigate this, we have considered significantly large bilayer leaflets and incorporated only one nanoparticle each time, which was subjected to all atomistic molecular dynamics simulations. We have observed that, lipid molecules located near to the gold nanoparticle interact directly with it, which results in deformation of lipid structure and slower dynamics of lipid molecules. However, lipid molecules far away from the interaction site of the nanoparticle get perturbed, which gives rise to increase in local ordering of the lipid domains and decrease in fluidity. The bilayer thickness and area per head group in this region also get altered. Similar trend, but with different magnitude is also observed when different size nanoparticle interact with the bilayer.

Effect of polyvinylpyrrolidone at methane hydrate-liquid water interface. application in flow assurance and natural gas hydrate exploitation - Choudhary, Nilesh; Das, Subhadip; Roy, Sudip; Kumar, Rajnish (Fuel, 2016)

Effect of shape of protrusions and roughness on the hydrophilicity of a surface - Chowdhury, Sheelan Sengupta; Pandey, Prithvi Raj; Kumar, Rajnish; Roy, Sudip (Chemical Physics Letters, 2017)
We have investigated wetting of model rough surfaces made up of hydrophilic triangular and hexagonal pillars (protrusions). The surface roughnesses are altered by varying the area of the rough surface, the height of the pillars, and the surface interactions to the water. We have established a correlation between structure i.e., the shape of a pillar, which actually depends on the number of edges (due to shape), and the wetting phenomena. We have found that surface with higher number of edges repels water at lower roughness value. We explain the correlation by analyzing the variation of interactions energy components and density profiles of water on the structured surfaces. (C) 2017 Elsevier B.V. All rights reserved.

Effect of sodium dodecyl sulfate surfactant on methane hydrate formation: a molecular dynamics study - Choudhary, Nilesh; Hande, Vrushali R.; Roy, Sudip; Chakrabarty, Suman; Kumar, Rajnish (Journal of Physical Chemistry B, 2018)
In experimental studies, it has been observed that the presence of sodium dodecyl sulfate (SDS) significantly increases the kinetics of hydrate formation and the final water-to-hydrate conversion ratio. In this study, we intend to understand the molecular mechanism behind the effect of SDS on the formation of methane hydrate through molecular dynamics simulation. Hydrate formation conditions similar to that of laboratory experiments were chosen to study hydrate growth kinetics in 1 wt % SDS solution. We also investigate the effect of interactions with isolated SDS molecules on methane hydrate growth. It was observed that the hydrophobic tail part of the SDS molecule favorably interacts with the growing hydrate surface and may occupy the partial hydrate cages while the head groups remain exposed to water.